Information System for Consumables Control of the Department of Public Works, Roads, and Water Resources - Fungky Ariya Wardana; Ade Eviyanti (CV. Media Digital Publikasi Indonesia, 2026)
This research aims to develop a web-based Information System for Consumable Goods Control at the Department of Public Works, Highways, and Water Resources of Sidoarjo Regency. The primary constraint in this institution lies in the manual inventory recording system, which is prone to data irregularities, reporting delays, and suboptimal stock control. To address these issues, this study employs the Research and Development (R&D) method with a Waterfall development model, encompassing the stages of preparation, system design, implementation, verification, and maintenance. The software is built using the PHP programming language and MySQL database, featuring master data management, transaction recording for incoming and outgoing goods, and real-time stock reporting. Based on the results of black-box testing, the system achieved a 100% success rate, proving that all functions operate according to specifications. The implementation of this system is expected to enhance data accuracy, operational efficiency, and transparency in managing consumable goods.